Pengaruh Pemasaran Digital dan Citra Destinasi Terhadap Keputusan Berkunjung di Desa Wisata Lebakmuncang Kabupaten Bandung - Arvianida Nafisah Rachmidiani; Emron Edison (Tourism Scientific Journal, 2023)
This research aims to analyze the influence of digital marketing and destination image on the visiting decision in Lebakmuncang Tourism Village, Bandung Regency. The research method used is quantitative with descriptive and verification analysis. The analytical technique employed is Multiple Linear Regression. The population of this study consists of tourists who visit Lebakmuncang Tourism Village, with a sample size of 100 respondents. Data were collected using questionnaires distributed to visitors of Lebakmuncang Tourism Village. The descriptive results of the study indicate that all variables are categorized as "good". The verification results of the study show that digital marketing has a positive and significant partial influence on the visiting decision, with a significance level of 0.001 < 0.05 and a calculated t-value of 3.296 > t-table = 1.988. Destination image also has a positive and significant partial influence on the visiting decision, with a significance level of 0.000 < 0.05 and a calculated t-value of 7.175 > t-table = 1.988. Simultaneously, digital marketing and destination image have a positive and significant influence on the visiting decision, with a significance level of 0.000 < 0.05 and a calculated F-value of 95.83 > F-table = 3.09. Additionally, the total coefficient of determination or total influence is 65.70%, indicating a strong influence. The remaining 34.3% represents the influence of other variables beyond the scope of this study, which should be examined by future researchers. In conclusion, it can be inferred that all three variables fall into the "good" category. However, further optimization is needed. Moreover, both digital marketing and destination image variables have a positive and significant influence on the visiting decision, both partially and simultaneously.